2013
DOI: 10.1111/hiv.12031
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of electrocardiogram testing among HIV‐infected patients at risk for medication‐induced QTc prolongation

Abstract: ObjectivesHIV-infected patients are commonly prescribed several medications and are thus at risk for drug interactions that may result in QTc prolongation. We sought (1) to identify the frequency of electrocardiogram (ECG) monitoring (2), to determine the prevalence of drug interactions involving QTc-prolonging medications, and (3) to quantify the prevalence of QTc prolongation. MethodsA cross-sectional study was conducted among HIV-infected adults. Demographics, medications, drug interactions and comorbiditie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
1
12
1
1
Order By: Relevance
“…However, such data are not available for Chinese HIV patients who may also experience high prevalence of subclinical atherosclerosis (21). In the present study, we observed relatively high prevalence of sinus tachycardia and ST-T segment elevation in HIV-positive individuals, although the prevalence is slightly lower than that reported by studies in south-east Africa (11) and USA (22,23). Such differences reflect global diversities in a confluence of CVD risk factors that may or may not be directly associated with HIV among PLWH, such as environmental exposures, lifestyle, nutrition, coinfections, access to ART and healthcare continuum (24)(25)(26).…”
Section: Discussioncontrasting
confidence: 65%
“…However, such data are not available for Chinese HIV patients who may also experience high prevalence of subclinical atherosclerosis (21). In the present study, we observed relatively high prevalence of sinus tachycardia and ST-T segment elevation in HIV-positive individuals, although the prevalence is slightly lower than that reported by studies in south-east Africa (11) and USA (22,23). Such differences reflect global diversities in a confluence of CVD risk factors that may or may not be directly associated with HIV among PLWH, such as environmental exposures, lifestyle, nutrition, coinfections, access to ART and healthcare continuum (24)(25)(26).…”
Section: Discussioncontrasting
confidence: 65%
“…16 The majority of our patients were accustomed to the daily physical activity like heavy labour work, truck drivers etc, which mitigated the inherent risk of arrhythmias and QTc prolongation, in contrast to the higher incidence of ECG repolarization heterogeneity noted with the sedentary habits 15 The electrophysiological mechanisms underlying drug induced QTc prolongation in relation to protease inhibitors and its clinical implications has been well described by Singh et al 9 All the patients with QTc prolongation in our study were on ART, a finding similar to the one by Patel et al which has reported QTc prolongation in 27.5% patients who were taking ART in their study of 454 HIV patients. 8 Reinsch et al 16 showed that the QTc was pronged in patients with lower CD4 count as compared to patients with higher CD 4 count and this is similar to our finding as most of our patients with QTc prolongation had lower CD 4 count (<200). The studies had shown that lower CD4 count were associated with ECG abnormalities and this may be related to the drugs, autonomic dysfunction like sympathetic and parasympathetic dysfunctions.…”
Section: Discussionsupporting
confidence: 90%
“…6,7 QT prolongation in HIV patients may be possibly related to the various drugs prescribed to these patients or to an acquired form of long QT syndrome (LQTC). 6,8 HIV-infected patients receiving cART have been associated with prolonged QTc interval and increased QT dispersion, independent of autonomic dysfunction and antiretroviral drugs, which may have led to the potentially higher risk of ventricular arrhythmia and cardiac mortality. Drugs like some antibacterial, antifungal, psychotropic and antihistamines have been found to be associated with QT prolongation or torsades de pointes (TdP), a life threatening ventricular arrhythmia.…”
Section: Introductionmentioning
confidence: 99%
“…Sixty-three studies reported HCV infection prevalence [63-65, 69, 72, 73, 75, 77, 79-84, 88, 90, 102-104, 107, 109, 110, 114, 117-119, 123, 127, 133, 140-173]. We calculated sPrev for HCV-exposed, defined in 69% of individual studies as positive by HCV antibody test, and for chronic HCV infection, defined in 80% of studies as positive by HCV antibody and HCV RNA tests (see Supplemental Table S6 for all definitions).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-six publications reported HBV infection prevalence [63, 65, 69, 71, 79-81, 89, 102, 106, 110, 123, 141, 144, 147, 150, 151, 154, 157, 159, 162, 165, 170, 172, 174, 175]. HBV infection was defined in 72% of individual studies as positive by HBV surface antigen test (see Supplemental Table S7 for all definitions).…”
Section: Resultsmentioning
confidence: 99%